Fear of cancer recurrence, anxiety and depressive symptoms in adolescent and young adult cancer patients - Sun, Hengwen (Neuropsychiatr Dis Treat, 2019)
Background: Previous studies have indicated that younger age is consistently associated with high levels of fear of cancer recurrence (FCR), anxiety and depression. However, the associations among these variables in adolescent and young adult (AYA) cancer patients are not clear. This study explores the prevalence and correlates of FCR, anxiety and depressive symptoms in Chinese AYA cancer population. Methods: This is a cross-sectional study that includes 249 patients aged between 15 and 39 yrs at the time of cancer diagnosis. Patient’s sociodemographic, clinical as well as psychological characteristics were collected by an information sheet, the Fear of Progression Questionnaire-Short Form (FoP-Q-SF), General Anxiety Disorder Questionnaire (GAD-7) and Patient Health Questionnaire (PHQ-9). Descriptive statistics and multivariate analyses were conducted. Results: Eighty-nine (35.74%) patients experienced dysfunctional level of FCR, eighty-two (32.93%) patients experienced anxiety symptoms and ninety-six (38.55%) reported depressive symptoms. In multivariate analyses, being single, pessimistic, having more concurrent stressful life events and physical comorbidity were independently associated with higher FCR, anxiety and depressive symptoms. Patients who were not engaging in radiotherapy were more likely to report higher anxiety level. Conclusion: FCR, anxiety and depressive symptoms are frequently reported problems among AYA cancer patients. Age-appropriate and flexible psychological interventions are needed for this high-risk population.